Identity Fusion and Adjustment in International Students at U.S. Colleges and Universities. (November 2021) - Kiang, Lisa; C. Brunsting, Nelson; Tevis, Tenisha; Zachry, Corinne; He, Yueying; Takeuchi, Risa
The present study explores how international students' (IS; N = 169; M age = 19.81 years, 36% male) identity fusion, the extent to which they feel connected with a particular social group, is concurrently and longitudinally correlated with belonging, loneliness, well-being, and perceived social support. IS reported higher fusion with other IS than with domestic students (DS). Fusion with IS at Time 1 (T1) was associated with greater IS support at T1 and Time 2 (T2). Fusion with DS was positively correlated with T1 belonging, well-being, and DS support at both time points, and was negatively linked with loneliness at T1 and T2. IS and DS fusion also interacted in predicting T1 belonging and loneliness. Students with proportionally greater DS than IS fusion reported greater DS support, and proportionally greater IS fusion was related to greater IS support. Discussion centers on promoting adjustment and intergroup relationships in higher education.